2007
DOI: 10.1007/s10643-006-0145-4
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Education and Care for Children with Disabilities: Facilitating Inclusive Practice*

Abstract: In this case study, a co-operative inquiry process was used to facilitate the expansion of inclusive early childhood education and care practices in a rural community in the Midwest. A university and a community researcher first engaged in interviews and site visits, during which they learned how a three-member inclusion team of early care and education professionals initiated changes in practice from self-contained to inclusive special education and therapy. Key practices included responding to families' prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 17 publications
(11 reference statements)
0
13
0
2
Order By: Relevance
“…This could indicate there are other contributing factors to the development of attitudes towards IE in the pre-service pre-school teacher population that this study, and those before it, have not been identified or examined. The preschool setting provides a range of challenges and needs which differ to those of the primary and secondary settings (DeVore & Russell, 2007;Ross-Watt, 2005), however, the majority of research has been centred upon these populations (de Boer et al, 2010;Pearce & Forlin, 2005). It is possible that, until now, the unique factors that shape pre-service pre-school teachers attitudes have been masked by the number of studies that incorporate overwhelmingly primary and secondary pre-service teacher samples.…”
Section: Discussionmentioning
confidence: 99%
“…This could indicate there are other contributing factors to the development of attitudes towards IE in the pre-service pre-school teacher population that this study, and those before it, have not been identified or examined. The preschool setting provides a range of challenges and needs which differ to those of the primary and secondary settings (DeVore & Russell, 2007;Ross-Watt, 2005), however, the majority of research has been centred upon these populations (de Boer et al, 2010;Pearce & Forlin, 2005). It is possible that, until now, the unique factors that shape pre-service pre-school teachers attitudes have been masked by the number of studies that incorporate overwhelmingly primary and secondary pre-service teacher samples.…”
Section: Discussionmentioning
confidence: 99%
“…Para ayudar a las escuelas a ser más inclusivas, se han desarrollado diversos recursos y programas para aplicar en escuelas inclusivas (DeVore & Russell, 2007;Karten, 2007).…”
Section: Discussionunclassified
“…To help schools be more inclusive, several resources and programmes have been developed to be utilized in inclusive schools (Devore & Russell, 2007;Karten, 2007).…”
mentioning
confidence: 99%
“…In addition, inclusive and diverse environments have been more prevalent and encouraged in early education [6][7][8][9]. It is important, then, that teachers are prepared to meet the needs of students with disabilities [8].…”
Section: Current Issues In the Us Kindergarten Educationmentioning
confidence: 99%